FACTOR PROMOTING WOUND HEALING: RADICAL SCAVENGING AND ANTI-INFLAMMATORY ACTIVITY AND GROWTH FACTOR PROMOTION OF HELIOTROPIUM INDICUM - WISIDSRI, NAKUNTWALAI; THUNGMUNGMEE, SURADWADEE; KHOBJAI, WARACHATE (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aims to investigate the effects of the Heliotropium indicum extract (HIE) on factor promoting wound healing in radical scavenging and inflammatory activity and growth factor promotion. Methods: The radical scavenging capacity of HIE was evaluated by scavenging of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) radicals. Furthermore, the anti-inflammatory of HIE was determined in a cellular model. RAW264.7 macrophage cells were treated with various concentrations of HIE before activating the treated cell with lipopolysaccharide (LPS). The nitrite concentration of activated macrophage was determined by the Griess reagent kit. The cell viability of RAW264.7 was evaluated by resazurin reduction assay as well as NIH3T3 fibroblast cells. In addition, production of the growth factors (transforming growth factor-β [TGF-β] and basic fibroblast growth factor [bFGF]) of fibroblast was determined by Elisa kit. Results: HIE exhibited radical scavenging activity in the DPPH and NO radicals with half maximal inhibitory concentration (IC50) at 0.22 mg/ml and 0.52 mg/ml, respectively. In a cellular study, HIE inhibited NO production in LPS-stimulated macrophage without cytotoxic effect to the cells with IC50 at 87 μg/ml. Furthermore, HIE promoted fibroblast cell viability at 72 h of treatment and, TGF-β and bFGF production at 24 h of treatment. Conclusion: These results obtained in this study suggested that HIE promoted the factors which involved in wound healing processes, including antiinflammatory effect with scavenged radical forming and inhibited activated-macrophage. Furthermore, HIE also stimulated growth factor production in fibroblast. These finding supported using traditional and folk medicine of H. indicum in wound treatment.